2007
DOI: 10.1016/j.exer.2006.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Fate of hypertonicity-stressed corneal epithelial cells depends on differential MAPK activation and p38MAPK/Na–K–2Cl cotransporter1 interaction

Abstract: The capacity of the corneal epithelium to adapt to hypertonic challenge is dependent on the ability of the cells to upregulate the expression and activity of cell membrane-associated Na-K-2Cl cotransporter1 (NKCC1). Yet, the signaling pathways that control this response during hypertonic stress are still unclear. We studied stress-induced changes in proliferation and survival capacity of SV40-immortalized human (HCEC) and rabbit (RCEC) corneal epithelial cells as a function of (i) the magnitude of the hyperton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
(72 reference statements)
0
23
0
Order By: Relevance
“…The present study, in conjunction with our previous work, demonstrates that, both, KCC1 and NKCC1 are essential components of the EGF-induced mitogenic signal in HCEC. 7 We previously demonstrated that a hypertonic challenge activates p38MAPK signaling, resulting in increases NKCC1 activity and cell swelling, 5,43 whereas EGF stimulation induces instead similar activation of NKCC1 and, consequently, enhanced cell proliferation. 7 In contrast, a hypotonic challenge induces KCC activation, leading to cell shrinkage and p44/42MAPK stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study, in conjunction with our previous work, demonstrates that, both, KCC1 and NKCC1 are essential components of the EGF-induced mitogenic signal in HCEC. 7 We previously demonstrated that a hypertonic challenge activates p38MAPK signaling, resulting in increases NKCC1 activity and cell swelling, 5,43 whereas EGF stimulation induces instead similar activation of NKCC1 and, consequently, enhanced cell proliferation. 7 In contrast, a hypotonic challenge induces KCC activation, leading to cell shrinkage and p44/42MAPK stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…5,43 Given that, EGF stimulates both NKCC1 and KCC1-leading to net increases in osmolyte influx and efflux, respectively, and changes in cell volume-coordinated regulation of ion transport pathway activity and their induced transient changes in cell volume are part of the mitogenic response required for corneal epithelial renewal. The involvement of such ion transporter mechanisms in mediating responses to mitogens indicates that their activation is an important component of the second messenger cascade linking receptor stimulation to increases in proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its inhibition suppressed such response. RVI is mediated by p38 protein-protein interaction with the Na:K:2Cl cotransporter 1 (NKCC1), which induces increases in osmolyte uptake followed by rises in NKCC1 gene and protein expression (Bildin et al, 2003;Capo-Aponte et al, 2007b). This dependence of RVI induction on p38 activation also exists in the renal medullary thick ascending limb of Henle's loop (Bustamante et al, 2003;Roger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%